Community Psychology Today: Ethical Guidelines for Action [Psicología Comunitaria Hoy: Orientaciones Éticas Para la Acción] - Pasmanik-Volochinsky, D; Winkler-Muller, M (Pontificia Universidad Catolica de Valparaiso, 2014)
We present the results of a study about the ethical dimension in the practice, training and research in community psychology (CP) in Chile between 2008 and 2011. We intentionally used a variety of sources of information production. 93 subjects - users, students and psychologists- participated in this study; and 194 documents - syllabuses, theses and codes- were analyzed. A combination of a qualitative method, survey techniques and analytical strategies produced as a relevant result the need to set specific ethical guidelines to guide the practice, training and research in CP, which we propose as a corollary.